Effect of the Crystalline Structure and Size of Group 4 and 5 Oxides to Oxygen Reduction Reaction. (19th June 2018) - Hirano, Shoko; Niwa, Etsuko; Maruyama, Takahiro; Saida, Takahiro
Abstract : In this study, the effects of the crystal structure and the crystallite size were investigated using ZrO2 and Nb2 O5 as a catalyst for oxygen reduction reaction (ORR). Those catalysts were characterized by XRD, UV-vis and XPS. Then the ORR activity was evaluated by cyclic voltammograms in Ar and O2 saturated 0.1 M HClO4 electrolyte using the static three-electrode cell. The crystal structure and crystallite size were controlled by the calcination temperature (400 - 700ºC). In the case of Nb2 O5, the crystal structure was independent of temperature, and at 600ºC mostly occupied asymmetric NbO6 octahedra in this structure. And Nb2 O5 at 600ºC showed the highest catalytic activity fot ORR. The crystal structure didn't affect to ORR activity. On the other hand, it seems to be presence the crystallite size of the optimal value. However, the optimal crystallinity may be important rather than its size.